Construct validity, sensitivity and specificity of the USCD Performance‐based Skill Assessment 2 in a mixed Portuguese sample. (6th May 2020) - da Motta, Carolina; Castilho, Paula; Pato, Michele T.; Barreto Carvalho, Célia
Abstract: Assessment batteries of functional capacity provide robust indicators of real‐world functioning in major psychiatric illnesses and important information on an individual's ability to live autonomously and pursue relevant psychosocial goals. Objectives: This study explores the psychometric properties of the Portuguese USCD Performance‐based Skill Assessment 2 (UPSA‐2‐PT) in a mixed sample of Portuguese participants. Method: A sample of 110 participants, 37 patients diagnosed with schizophrenia, 27 first‐degree relatives of patients and 46 controls were administered the UPSA‐2‐PT and self‐report questionnaires. The UPSA‐2‐PT reliability was assessed through inter‐rater reliability and internal consistency, convergent validity with community integration and a receiver operating curve analysis was conducted to establish scores' sensitivity and specificity. Youden's Index was used to determine an optimal UPSA‐2‐PT cutoff score. Results: Findings show an excellent inter‐rater reliability, good internal consistency and construct validity, consistent with previous studies in Western countries. The UPSA‐2‐PT also showed a good discriminant ability between patients and controls, and an overall percentage of correct classification of 86.7% based on the 81.59 cutoff. Discussion: Findings are congruous with previous versions, strengthening the body of evidence supporting the construct validity and providing a useful tool for research and clinical purposes to practitioners.